Reproductive ecology of the seabob shrimp Xiphopenaeus kroyeri (Heller, 1862) in a coastal area of Southern Brazil - Grabowski, Raphael Cezar [UNESP] (2016)
The predictability of certain environmental factors that affect the life cycle of the seabob shrimp Xiphopenaeus kroyeri (Heller, 1862) was evaluated in a study of its reproductive biology in an area adjacent to Babitonga Bay, State of Santa Catarina, Brazil. Monthly sampling was conducted from July 2010 through June 2011 at depths of 5, 8, 11, 14, and 17 m. 76 004 individuals were obtained, with a pronounced peak in absolute abundance in austral autumn (34 208), coinciding with the annual closed season from March to May. Grain size composition of the sediment showed the closest relationship to the distribution of individuals (multiple linear regression, P < 0.05), related to their burying habit. The observed correlations between the abundance of reproductive males (bearing spermatophores) and females with spent gonads (cross-correlation, P < 0.05), and between reproductive males and reproductive females (with a 1-month lag) suggest that the peak of reproductive males preceded the peak of female ones. This result agrees with the pattern expected for females, which copulate in post-ecdysis (spent gonads). Spawning seemed to take place at greater depths, as evidenced by the concentration of reproductive females in these areas. The reproductive activities observed here confirm that this species follows a tropical/subtropical reproductive pattern, spawning continuously throughout the year, with the highest peaks in spring and autumn. The data indicate that the juvenile recruitment period observed in August-September resulted from the reproductive output noted in April-May. Additionally, the reproductive period recorded in November led to the juvenile peak observed in March-May.